Remote Ischemic Conditioning in the Prevention for Stroke-Associated Pneumonia: A Pilot Randomized Controlled Trial - Zhang, Bowei; Zhao, Wenbo; Ma, Hongrui; Zhang, Yunzhou; Che, Ruiwen; Bian, Tingting; Yan, Heli; Xu, Jiali; Wang, Lin; Yu, Wantong; Liu, Jia; Song, Haiqing; et al. (Frontiers in Neurology, 2022)
Background: Despite the continuing effort in investigating the preventive therapies for stroke-associated pneumonia (SAP), which is closely associated with unfavorable outcomes, conclusively effective therapy for the prevention of SAP is still lacking. Remote ischemic conditioning (RIC) has been proven to improve the survival in the sepsis model and inflammatory responses have been indicated as important mechanisms involved in the multi-organ protection effect of RIC. This study aimed to assess the safety and the preliminary efficacy of RIC in the prevention of SAP in patients with acute ischemic stroke. Methods: We performed a proof-of-concept, pilot open-label randomized controlled trial. Eligible patients (age＞18 years) within 48 hours after stroke onset between March 2019 and October 2019 with acute ischemic stroke were randomly allocated (1:1) to the RIC group and the control group. All participants received standard medical therapy. Patients in the RIC group underwent RIC twice daily for 6 consecutive days. The safety outcome included any adverse events associated with RIC procedures. The efficacy outcome included the incidence of SAP, changes of immunological profiles including mHLA-DR, TLR-2 and TLR-4 as well as other plasma parameters from routine blood test. Results: In total, 46 patients aged 63.1±12.5 years, were recruited (23 in each group). Ultimately, 19 patients in the RIC group and 22 patients in the control group completed this study. No severe adverse event was attributed to RIC procedures. The incidence of SAP was lower in the remote ischemic conditioning group (2 patients [10.5%]) than that in the control group (6 patients [27.3%]), but no significant difference was detected in both univariate and multivariate analysis (p=0.249 and adjust p=0.666). The IL-6 and IL-1β levels at day 5 after admission in the RIC group were lower than those in the control group (p＜0.05). Interpretation: This proof-of-concept pilot randomized controlled trial was to investigate RIC as a prevention method for SAP. Remote ischemic conditioning is safe in the prevention of SAP in patients with acute ischemic stroke. The preventive effect of RIC on SAP should be further validated in future studies.